Computational study of Cu2+, Fe2+, Fe3+, Mn2+ and Mn3+ binding sites identification on HSA 4K2C. Issue 1 (May 2020) - Wibowo, Syahputra; Sumitro, Sutiman B; Widyarti, Sri
Abstract: This research aims to computationally characterize HSA 4K2C protein and describe as well as its ability to bind transition metal ions. Data mining is performed to obtain HSA 4K2C from PDB and transition metal ions such as Cu 2+ (ID: 27099), Fe 2+ (ID: 27284), Mn 2+ (ID: 27854), Mn 3+ (ID: 105130) and Fe 3+ (ID: 29936) from PubChem. The analysis consists of ProtParam, Motif Search, CFSSP, DLP-SVM, and docking. Docking used PyRx Autodock Vina. Analysis of receptor-ligand interactions used DS 2016. The results of the ProtParam analysis provide some information on HAS 4K2C, which is it has 585 amino acids with an isoelectric point (pI) of 5.67, an index of protein instability of 38.85, then total amino acids (aa) residues of negatively charged (Asp + Glu) are 98 while the positively charged ones (Arg + Lys) are 83. Motive Search shows that there are three HSA motifs namely motif 1 (aa. 551-575), motif 2 (aa. 353-377), and motif 3 (aa. 61-185). CFSP shows α -helix structure is the dominant structure compared to β-sheet, turn and coil in 4K2C. DLP-SVM shows two domain linkers where DL-1 (aa. 410-451) and DL-2 (aa. 96-122). Docking shows the ability of HSA 4K2C in binding metal ions such as Cu 2+, Fe 2+, Mn 2+, Mn 3+ and Fe 3+ .